191 MANAGING SNAKE ENVENOMATION: AN INTENSIVE CARE UNIT EXPERIENCE. (1st January 2005) - Godkar, D.; Sathe, S.; Dave, B.; Yeolekar, M. E.
Abstract : Snakebite, though considered to be occurring primarily in rural settings, may develop complications requiring intensive care. Reported here are 164 serial cases of snake poisoning managed at the ICU of our hospital over a five-year period. Snake was identified in 72 patients (krait-24, cobra-3, Russell viper-16, saw-scaled viper-29), but could not be identified in 96 cases. The time lapse between bite and first treatment received ranged from 1-6 hours. Patients were transferred to tertiary care centers with development of complications like severe bleeding, oliguria, anuria or neuromuscular weakness with the time range being 2 hours to 5 days. Out of 164 patients, 105 presented with vasculotoxic complications and 59 with neurotoxic complications. Patients with vasculotoxic snakebite had local swelling (100%), ecchymosis(58%), cellulitis (44%), local bleeding (54%) and gangrene of digits (5%). Systemic envenomation manifested as defective coagulation (100%), spontaneous systemic bleeding (78%), hypotension (24%), oliguria (42%), thrombocytopenia (52%), presence of fibrin degradation products (36%), low fibrinogen (26%) and intravascular hemolysis (42%). Average time required for reversal of bleeding diatheses was 2.44 days. Requirement of anti-snake venom (ASV) being 4-100 vials. 51 patients were given fresh frozen plasma and 26 patients required blood transfusion. Acute renal failure developed in 24 patients of which 16 patients required dialysis. Patients with neurotoxic snake bite had ptosis (100%), dysphagia (89%), weakness in limbs (64%), respiratory distress (75%), loss of consciousness (20%), drowsiness (38%), and convulsion (9%).Time interval for manifestation of symptoms was 10 minutes to 8 hours. 32 patients had hypoxia and/or hypercapnea. 34 patients required ventilatory support (50%) and range of ventilatory support was 16 hours to 15 days. ASV required was between 4-34 vials and neostigmine was between 2-192 mg. Unusual features noticed were in the nature of hematomyelia, massive left upper limb necrosis requiring amputation, resistant ventricular arrhythmia, myocarditis with pulmonary edema. 4 patients developed anaphylactic reaction to ASV and 2 patients developed severe cholinergic crisis following neostigmine injection. Despite the critical care management 12 (7.3%) patients expired, 8 vasculotoxic (7.6%) and 4 neurotoxic (6.8%) due to various etiologies.